PEMBELAJARAN APRESIASI PUISI REKREATIF DI SMK - Andayani Andayani (Universitas Sebelas Maret, 2009)
Theresearchaimsatdescribingtherealizationofrecreativepoetryteachingin SMK Negeri 1 Surakarta. The focus of the research is about the things related to the expressive and recreative poetry teaching which include the planning, the implementing, the barriers, and the efforts done by the teacher in handling recreative poetry teaching. The research is a case study research (qualitative research). The result of this research concludes that it is necessary to gain the perception of Indonesian Language teacher about the curriculum, the competence in recreative poetry teaching, and the theory and appreciation of poetry. With the increase of those things, it is hoped that the teacher can guidestudentstohaveahighabilityaboutrecreativepoetryappreciation.